Mass flow and hydrofracturing during Late Devensian moraine emplacement, NE Scotland. Issue 6 (December 2020) - Phillips, Emrys; Kearsey, Timothy I.
Abstract: This paper presents the results of a detailed study of a sequence of Late Devensian (Weichselian) sands, gravels and diamictons exposed within a recessional moraine near Loch Killin, near Fort Augustus, Monadhliath Mountains, NE Scotland. Macroscale sedimentological and structural field observations are combined with micromorphological and micro-structural analysis to investigate the ice-marginal processes which led to the construction of this landform. Microstructures present within the stratified diamictons mantling the glacitectonised core of the moraine reveal a complex history of microfabric development resulting from ductile shearing during the emplacement of these ice-marginal mass flow deposits. Shearing occurred throughout the entire mass flow with flowage occurring towards the WNW. The laminated sediments which infill a number of steeply inclined hydrofractures which cut the moraine are interpreted as having accommodated several phases of fluid flow, with a palaeoflow direction towards the WNW. A detailed model of ice-marginal landform development has been established involving glacitectonism as a result of ice-push during a readvance of the glacier, followed by mass flow of sediments released as a result of melting of the snout during a period of still stand, followed by hydrofracturing accompanying the escape of pressurised meltwater from beneath the ice, probably during the initial stages of glacier retreat.